Revisiting Structural, Vibrational, and Photochemical Data of Matrix-Isolated Simple Hydantoins — Common Features and Substituent Effects - FAUSTO, RUI; ILDIZ, GÜLCE ÖĞRÜÇ; Nogueira, Bernardo A. (American Institute of Physics, 2024)
Characteristic features of the structure (geometries, electronic structures), vibrational spectra (infrared), and photochemistry of a series of simple hydantoins (parent hydantoin, 1-methylhydantoin, 5-methylhydantoin, and 5-acetic acid hydantoin), and effects of substituent on these properties, are reviewed in a comparative comprehensive perspective taken as a basis the low-temperature matrix isolation infrared spectroscopy and electronic structure quantum chemistry data we have reported before for the individual compounds. It is shown that the hydantoin moiety shows a general tendency towards planarity (or quasi-planarity), mostly determined by the π-electron delocalization in the system, in which the two nitrogen atoms are extensively involved and, in the molecules studied, also counts with the involvement of the π-type orbitals of the -C5H2- or -C5HR- (with R ˭ CH3 or CH2COOH in 5-methylhydantoin and 5-acetic acid hydantoin, respectively) fragment (hyperconjugation). The geometries and charge density analyses of the compounds also show that the main electronic effects in the hydantoin ring are the N-to-(C ˭ O) π-electron donation, and the σ system back-donation from the σ-lone electron pairs of the oxygen atoms to the ring. The frequencies of the bands observed in the matrix-isolation infrared spectra (Ar; 10 K) of the different compounds that are assigned to the carbonyl and amine fragments are discussed comparatively, and substituent effects are assessed. Finally, the UV-induced (λ = 320 nm) photochemistry of the hydantoins is shown to share a common pattern, leading to the concerted extrusion of isocyanic acid and carbon monoxide, accompanied by an imine derivative that depends upon the specific hydantoin reactant. An additional photofragmentation pathway, most probably involving nitrene intermediacy, also takes place for 1-methylhydantoin, indicating a specific effect of the substitution at position 1 of the hydantoin ring on the photofragmentation of hydantoins. © 2024 Author(s).
Keywords: Hydantoins; Matrix Isolation Infrared Spectroscopy; Molecular Structure; Photochemistry.; Spectroscopy